Efektivitas Diversi Berdasarkan UU SPPA: Analisis Yuridis dan Perspektif Keadilan Restoratif di Indonesia - Muhammad Faizin; Fahmi; Rudi Pardede (Jurnal Pustaka Cendekia Pendidikan, 2025)
Diversion is a mechanism for resolving juvenile cases outside the formal judicial process, as regulated in Law Number 11 of 2012 on the Juvenile Criminal Justice System (UU SPPA). The primary objective of diversion is to protect children from the negative impacts of the criminal justice system and provide rehabilitation opportunities within the framework of restorative justice. However, its effectiveness remains debatable due to limited understanding among law enforcement officers, inadequate rehabilitation facilities, and societal resistance toward this approach. This study employs a normative juridical method using a statutory approach and case studies of court decisions on diversion. The findings reveal that despite its implementation, diversion has not been optimally executed due to legal interpretation inconsistencies, lack of rehabilitation infrastructure, and minimal victim involvement in case resolution. Therefore, policy reforms are necessary, including capacity-building for law enforcement, strengthening rehabilitation facilities, and optimizing victim and community participation in the diversion process. These measures aim to enhance diversion as a more effective restorative justice instrument within Indonesia's juvenile criminal justice system.